Effect of a proton-pump inhibitor on intestinal microbiota in patients taking low-dose aspirin - Tsujimoto, Hiroyuki; Hirata, Yuki; Ueda, Yasuhiro; Kinoshita, Naohiko; Tawa, Hideki; Tanaka, Yasuyoshi; Koshiba, Ryoji; Ota, Kazuhiro; Kojima, Yuichi; Kakimoto, Kazuki; Takeuchi, Toshihisa; Miyazaki, Takako; et al. (European journal of clinical pharmacology, 2021)
Background and aim Low-dose aspirin (LDA) administration prevents cerebral infarction and myocardial infarction, but many studies found an association with mucosal injury. Proton-pump inhibitors (PPIs) can prevent gastric and duodenal mucosal damage, but they may exacerbate small-intestinal mucosal injury by altering the microbiota. We aimed to assess the effect of PPIs on the intestinal flora of LDA users. Methods Thirty-two recruited patients, who received LDA (100 mg/day) but did not take PPIs, were divided into 15 patients additionally receiving esomeprazole (20 mg/day) and 17 patients additionally receiving vonoprazan (10 mg/day). On days 0, 30, 90, and 180, the microbiota of each patient was examined by terminal restriction fragment length polymorphism analysis, and the serum gastrin, hemoglobin, and hematocrit levels were measured. Results Additional PPI administration increased the proportion of Lactobacillales in the microbiota of LDA users. This trend was more prevalent in the vonoprazan group ( p < 0.0001) than in the esomeprazole group ( p = 0.0024). The Lactobacillales proportion was positively correlated with the gastrin level ( r = 0.5354). No significant hemoglobin or hematocrit level reduction was observed in subjects receiving LDA with additional PPI. Conclusions Additional PPI administration increased the Lactobacillales proportion in the microbiota of LDA users. The positive correlation between the gastrin level and the proportion of Lactobacillales suggested that the change in the intestinal flora was associated with the degree of suppression of gastric acid secretion. Additional oral PPI did not significantly promote anemia, but the risk of causing PPI-induced small-intestinal mucosal injury in LDA users should be considered.